2003
DOI: 10.1128/aac.47.2.541-547.2003
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Analysis of Nonlinear Behavior of Piperacillin during Intermittent or Continuous Infusion in Patients with Cystic Fibrosis

Abstract: The purpose of this study was to describe the nonlinear pharmacokinetics of piperacillin observed during intermittent infusion and continuous infusion by using a nonparametric population modeling approach. Data were 120 serum piperacillin concentration measurements from eight adult cystic fibrosis (CF) patients. Individual pharmacokinetic parameter estimates during intermittent infusion or continuous infusion were calculated by noncompartmental analysis and with a maximum iterative two-stage Bayesian estimator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
50
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 24 publications
(18 reference statements)
10
50
0
2
Order By: Relevance
“…While Vinks and colleagues published an MM model for this drug, there are several reasons for the dissimilar findings (35). First, their patient population was a specialized population (cystic fibrosis patients) that may have different K m and V max values for the anion-selective pumps in their renal tubules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While Vinks and colleagues published an MM model for this drug, there are several reasons for the dissimilar findings (35). First, their patient population was a specialized population (cystic fibrosis patients) that may have different K m and V max values for the anion-selective pumps in their renal tubules.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the observed mean K m and V max values for the MM model were 307.03 Ϯ 147.4 and 812.75 Ϯ 801.64, respectively, which are substantially different from the observed mean K m and V max values (92.3 Ϯ 85.6 and 2,284 Ϯ 1,046) in the study of Vinks et al Second, the observed differences in the clearance models between studies may be secondary to the different infusion methods (intermittent versus continuous). In the study of Vinks et al, it was only with a continuous-infusion mode of administration that the benefits of the MM model were manifested (35). The nonlinear behavior of piperacillin in non-cystic fibrosis patients, therefore, may not become as evident with intermittent infusion as with continuous infusion, especially with continuous-infusion steadystate concentrations exceeding the K m .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A one-compartment, first-order, intravenous model was used to calculate %TϾMIC. While there is disagreement as to the accuracy of a one-compartment model for pharmacodynamic analysis (30), the infusion time of piperacillin-tazobactam is relatively uniform, which negates much of the differences (13,29). Tazobactam exposure was estimated by calculating the area under the concentration-time curve (AUC 0-24 ).…”
Section: Treatment Of Infections Caused By Extended-spectrum-␤-lactammentioning
confidence: 99%
“…7 In addition, saturable renal elimination has been identified previously in adults. [8][9][10] To date, the pharmacokinetics of piperacillin/tazobactam have been described in (pre)term neonates and non-ICU children, but only in a small number of children admitted to the paediatric ICU (n=13 and n=12 patients), between 1 and 9 years of age. 7,[11][12][13][14][15] Any effort to define the dose rationale in infants and young children needs to account for the effect of developmental processes, which are known to affect drug exposure and potentially treatment response.…”
Section: Introductionmentioning
confidence: 99%